2019
DOI: 10.18280/ijht.370218
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Generation in MHD Flow of Carbon Nanotubes in a Rotating Channel with Four Different Types of Molecular Liquids

Abstract: The greatest endowment of present-day science is nanofluid. The nanofluid can ready to move unreservedly through smaller scale channels with the spreading of nanoparticles. Because of improved convection between the base fluid surfaces and nanoparticles, the nanosuspensions express high warm conductivity. Additionally, the advantages of suspending nanoparticles in base liquids are expanded warmth limit, surface zone, successful warm conductivity, impact, and collaboration among particles. The point of this exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
(48 reference statements)
1
3
0
Order By: Relevance
“…As a result deviation from dynamic equilibrium state induces a relative velocity between the particles and the blood that generates additional energy dissipation and consequently it results in an effective viscosity 54 , consequently, fluid grows denser and thicker, slowing the flow. The variation in the values of has also resulted the same behavior as observed for During their research, Saqib et al 9 and Nandkeolyar and Das 55 also reported this tendency .This result shows that by adjusting the values of the and successful drug delivery to the tumor cite can be made possible. The influence of the on blood and particle motion is seen in Fig.…”
Section: Graphical Results and Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…As a result deviation from dynamic equilibrium state induces a relative velocity between the particles and the blood that generates additional energy dissipation and consequently it results in an effective viscosity 54 , consequently, fluid grows denser and thicker, slowing the flow. The variation in the values of has also resulted the same behavior as observed for During their research, Saqib et al 9 and Nandkeolyar and Das 55 also reported this tendency .This result shows that by adjusting the values of the and successful drug delivery to the tumor cite can be made possible. The influence of the on blood and particle motion is seen in Fig.…”
Section: Graphical Results and Discussionsupporting
confidence: 69%
“…The velocity field for unsteady incompressible fluid flow mixed with magnetic in presence of pressure gradient and perpendicularly applied magnetic field in a cylindrical coordinate system ( ) is defined as 9 , 43 : …”
Section: Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Marwat and Asghar investigated the flow between inclined plane walls. Saeed et al studied the flow of nanofluid in a rotating channel.…”
Section: Introductionmentioning
confidence: 99%